Development of Smart Tourism as an Innovative Strategy to Increase Regional Economic Capacity in the Coastal Region of East Java - Santoso, Rudi (Majalah Ekonomi, 2026)
This study aims to analyze the development of smart tourism as an innovative strategy in increasing regional economic capacity, with a focus on case studies in the coastal areas of East Java, namely Banyuwangi, Situbondo, and Gresik. A qualitative-descriptive approach was used through in-depth interviews, field observations, and documentation studies to explore the practice of implementing tourism digitalization and its impact on local communities. The results of the study show that the integration of information and communication technology in the management of tourist destinations is able to expand promotion, encourage service innovation, and empower MSMEs and local communities. However, digital infrastructure gaps, low technological literacy, and lack of synergy between stakeholders remain significant challenges. This research contributes theoretically to expanding the understanding of the concept of smart tourism in the context of developing countries and practically provides a strategic model that can be adopted by local governments and tourism industry players. These findings confirm that the success of smart tourism is highly dependent on multi-sector collaboration, participatory approaches, and the inclusive and sustainable use of technology to drive the economic growth of coastal areas